Ineffective Treatment of Low-Molecular-Weight Heparin in Obese Subject with Traumatic Fractures of the Leg - Imbalzano, Egidio; Creazzo, Michele; Trapani, Giovanni; Lizio, Giuseppina; Saitta, Antonino (International Journal of Angiology, 2016)
American College of Chest Physicians Evidence-Based Clinical Practice Guidelines, 9th edition, 2012, suggest no prophylaxis rather than pharmacological thromboprophylaxis in management of venous thromboembolism (VTE) risk of isolated lower leg injuries distal to knee requiring leg immobilization. Low-molecular-weight heparin (LMWH) is a class of drugs commonly used as antithrombotics in surgery and in case of prolonged bed rest and hypomobility. A 35-year-old obese man with no history of health disease (height, 170 cm; weight, 95 kg; and body mass index, 32.9 kg/m2) was involved in a car accident, and as a result of the trauma he suffered the compound fracture of left tibia and fibula. Tibial intramedullary nailing was performed. The injury was near the knee, and the patient was advised long-term bed rest. For these reasons, he was treated with enoxaparin 40 mg once daily subcutaneously. On the 7th day of hospitalization, the leg became edematous and reddish. A Doppler ultrasonography evaluation was performed which showed a massive deep vein thrombosis of left leg and then a pulmonary angiotomography showed a massive pulmonary embolism. In this clinical case, there was a pharmacological treatment failure to prevent VTE after orthopedic surgery and related long-term rest using enoxaparin at prophylaxis dosage in a patient without history of health disease but at high risk of VTE for obesity, trauma, orthopedic surgery, and immobilization. Enoxaparin dosage to prevent VTE in patients with high risk should be reconsidered and especially in obese a weight-adjusted dosage can be better than a fixed dosage.
Keywords: thromboprophylaxis; deep vein thrombosis; enoxaparin; lower extremity; low-molecular-weight heparin; risk factors; young